Attitudes of Cancer Patients to Medicinal Cannabis Use: A Qualitative Study. Issue 2 (3rd April 2022) - Wilson, Amy; Davis, Cindy
ABSTRACT: As cancer patients face long-term health and psychosocial issues from their diagnosis and treatment, many patients are seeking medicinal cannabis to manage their symptoms and treatment side effects. This qualitative study aimed to explore attitudes, barriers, and concerns of cancer patients from one regional community in Australia to gain a better understanding of the experiences faced in using medicinal cannabis. Participants ( n = 16) engaged in focus groups or semistructured individual interviews, and an inductive thematic analysis of data was undertaken. Four themes emerged from the data: perceived benefits, access difficulties, uncertainty, and issues of support. The findings revealed a need to provide easy access to accurate information and address the barriers faced by cancer patients in using medicinal cannabis. IMPLICATIONS Despite the growing body of clinical evidence, cancer patients may be faced with bureaucratic and social challenges in gaining access to medicinal cannabis that will require social workers' individual advocacy. Social workers should consider the roles that might be appropriate for them in advocating for policy and legislation changes around access, cost, and other barriers. Social workers working in oncology should consider the roles that might be appropriate for them in linking cancer patients to community support and resources, and in assisting cancer patients interested in medicinal cannabis, including an advocacy role.